2019
DOI: 10.35542/osf.io/f7srb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Both Questionable and Open Research Practices are Prevalent in Education Research

Abstract: Discussions of how to improve research quality are predominant in a number of fields, including education. But how prevalent are the use of problematic practices and the improved practices meant to counter them? This baseline information will be a critical data source as education researchers seek to improve our research practices. In this preregistered study, we replicated and extended previous studies from other fields by asking education researchers about 10 questionable research practices and 5 open resear… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
32
3
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 19 publications
6
32
3
1
Order By: Relevance
“…While the point estimates of QRP prevalence vary, John et al's (2012) findings have been replicated among samples of Brazilian, German and Italian psychologists (Agnoli, Wicherts, Veldkamp, Albiero, & Cubelli, 2017;Fiedler & Schwarz, 2016;Rabelo et al, 2020) and among researchers in ecology, evolutionary biology, and education (Fraser et al, 2018;Makel et al, 2019) -see Table 4 for an overview.…”
Section: Self-reported Questionable Research Practicesmentioning
confidence: 98%
See 2 more Smart Citations
“…While the point estimates of QRP prevalence vary, John et al's (2012) findings have been replicated among samples of Brazilian, German and Italian psychologists (Agnoli, Wicherts, Veldkamp, Albiero, & Cubelli, 2017;Fiedler & Schwarz, 2016;Rabelo et al, 2020) and among researchers in ecology, evolutionary biology, and education (Fraser et al, 2018;Makel et al, 2019) -see Table 4 for an overview.…”
Section: Self-reported Questionable Research Practicesmentioning
confidence: 98%
“…Vermeulen et al (2015, p. 202) concluded that empirical papers in communication most likely suffer from "a high false positive rate," likely driven by QRPs, such as only publishing studies that "worked," and placing those that did not work in a file drawer. According to surveys in other social science disciplines, non-publication is fairly common (Fraser, Parker, Nakagawa, Barnett, & Fidler, 2018;John et al, 2012;Makel, Hodges, Cook, & Plucker, 2019). Franco et al (2014) report direct evidence for non-publication among experiments that were fielded in the Time-sharing Experiments for the Social Sciences -a project where peer-reviewed experiments are fielded in a population based sample -and compared the reported number of conditions in the publication to the actual number of conditions that were included in the survey.…”
Section: Questionable Research Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective re-porting makes it more likely that a prediction is supported by the data, and less likely that a prediction is proven wrong. Given a scientific reward system where successful predictions are deemed more valuable than unsuccessful predictions it is perhaps not surprising that researchers admit to selectively reporting results (Fiedler & Schwarz, 2015;Fraser, Parker, Nakagawa, Barnett, & Fidler, 2018;John, Loewenstein, & Prelec, 2012;Makel, Hodges, Cook, & Plucker, 2019), and selectively submit significant results for publication (Franco, Malhotra, & Simonovits, 2014;Greenwald, 1975). This behavior, which violates most code of conducts for research integrity, but is nevertheless commonplace, leads to a scientific literature that does not reflect reality.…”
mentioning
confidence: 99%
“…Ils prennent la peine de rajouter que le simple fait de suggérer sur la base de résultats déformés que ce type de conduite est fréquent, affaiblit non seulement les messages de prévention destinés à prévenir ces pratiques de recherche discutables, mais nuisent également gravement à l'image de la recherche scientifique et par extension la confiance en ses recommandations (Fiedler & Schwarz, 2016). Là encore, ces pratiques de recherche discutables sont loin d'être uniquement propres à la psychologie, elles concernent par exemple l'écologie et la biologie de l'évolution (Fraser, Parker, Nakagawa, Barnett, & Fidler, 2018), les recherches biomédicales (Gardner, Lidz, & Hartwig, 2005), les sciences économiques (List, Bailey, Euzent, & Martin, 2001), les sciences de l'éducation (Makel, Hodges, Cook, & Plucker, 2019), le management (O'Boyle et al, 2017) ou encore l'ingénierie civile (Swazey, Anderson, Lewis, & Louis, 1993), etc. Si ces pratiques de recherche discutables paraissent à première vue inoffensives, elles sont de plus en plus montrées du doigt en raison de leur écart avec les nouveaux standards de recherche qui aspirent à une plus grande rigueur scientifique.…”
Section: Les Facteurs à L'origine De Cette Criseunclassified